Formulation of dielectric composite material from ananas comosus waste for 5 ghz microstrip antenna - Nur Sofia Idayu, Didik Aprianto; Mohamad Khalid, Zakarzan; Nurhafizah, Abu Talip Yusof; Nurulfadzilah, Hasan; Mohamad Shaiful, Abdul Karim (Trans Tech Publications, Switzerland, 2025)
This study explores the formulation of dielectric composite material derived from Ananas comosus (pineapple) waste for 5 GHz microstrip antenna applications. Cellulose extracted from pineapple leaves was incorporated into an epoxy matrix to achieve a permittivity (εr) of 4.13. Morphological analysis revealed cellulose fiber particles averaging 1.60 μm in diameter, embedded within a composite matrix rich in carbon and oxygen. EDX analysis confirmed composition percentages of 62.07 wt.% carbon, 33.95 wt.% oxygen, and 3.98 wt.% sodium. Antenna performance evaluation demonstrated an optimal reflection coefficient, S11, of -32 dB at 5.30 GHz in simulations, meeting FCCs 5G band specifications. The three-dimensional radiation patterns from the simulations confirmed efficient power radiation, with a gain of 4.246 dBi, indicating the suitability of the dielectric composite for effective signal transmission and reception. Experimental results showed an S11 of -22 dB at 5.15 GHz, validating robust performance within the 5 GHz range. These findings underscore the potential of pineapple waste-derived composites in advancing sustainable antenna technology.